2011
DOI: 10.1016/j.seizure.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant activities of myo-inositol and scyllo-inositol on pentylenetetrazol induced seizures

Abstract: Myo-inositol (MI) and its isomers are used for the treatment of various neuropathological conditions. The purpose of the present research was to study anticonvulsant properties of MI and scyllo-inositol (SCI) on pentylenetetrazol (PTZ) induced seizures in rats. Half an hour after treatment with MI (30 mg/kg) or SCI (5 mg/kg) seizures were induced in Wistar rats with PTZ (60 mg/kg). Control animals were treated either by normal saline or mannitol (control polyol of the same molecular weight, 30 mg/kg), given at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…MI is characterized by anticonvulsant properties and this inositol could partially reduce the seizure grade and duration of PTZ or KA induced convulsions [7, 8]. The influence of inositol on molecular changes after SE could be simply mediated by antiseizure activity of compound and/or its action on GABA-A receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MI is characterized by anticonvulsant properties and this inositol could partially reduce the seizure grade and duration of PTZ or KA induced convulsions [7, 8]. The influence of inositol on molecular changes after SE could be simply mediated by antiseizure activity of compound and/or its action on GABA-A receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In later studies we revealed that MI pretreatment significantly decreases the severity of seizures induced either by pentylenetetrazole (PTZ) or by kainic acid (KA) [7, 8]. In the next series of experiments initially we induced the status epilepticus (SE) by KA and then tried MI daily treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Solomonia et al showed that MI significantly reduced the intensity and severity of seizures [58]. Importantly, Nozadze et al also demonstrated that MI delayed the latent period for seizure onset and decreased seizure duration [59]. Thus, unlike all other mechanisms discussed in this section (which emphasize excitatory/inhibitory imbalances), MI levels address the oftenignored area of the refractory period in favouring TAE over TASE.…”
Section: Myo-inositol Levelsmentioning
confidence: 94%
“…[71] In rats seizures induced by pentylenetetrazole were reduced in severity following the administration of scyllo-inositol, suggesting that it may have a role to play in antiepileptic therapy. [72] …”
Section: Scyllo-inositol and Neurological Disordersmentioning
confidence: 99%